A sustainable biorefinery approach for efficient conversion of aquatic weeds into bioethanol and biomethane. (1st May 2019) - Kaur, Manpreet; Kumar, Manoj; Singh, Dheer; Sachdeva, Sarita; Puri, S.K.
Graphical abstract: Highlights: Various pretreatment methods assessed to extract maximal energy from aquatic weeds. Coupled hydrothermal treatment and anaerobic digestion reduced biomass obstinacy. HT + AD treatment resulted in maximum ethanol yield of 0.167–0.231 g/g-biomass. Highest methane yield (209–257 dm 3 /kg TOCR ) was recovered through HT + AD. The integrated production of ethanol and methane enhanced total energetic yield. Abstract: The study outlines an economical biorefinery concept to evaluate the potential of three aquatic weeds Eichhornia crassipes, Lemna minor and Azolla microphylla for co-production of ethanol and methane. Four different scenarios were investigated viz., scenario A-hydrothermal treatment followed by anaerobic digestion and ethanol fermentation respectively (HT → AD → EF), scenario B- thermochemical treatment followed by anaerobic digestion and ethanol fermentation respectively (TC → AD → EF), scenario C- hydrothermal treatment followed by ethanol fermentation and anaerobic digestion respectively (HT → EF → AD) and scenario D- thermochemical treatment followed by ethanol fermentation and anaerobic digestion respectively (TC → EF → AD). Sequential hydrothermal treatment and anaerobic digestion (HT → AD) in scenario A enhanced the hemicellulose removal by 68.5–73.5% and simultaneously enriched the cellulose content by 41.2–54.5%. This contributed to highest ethanol yield (0.167–0.231 g/g biomass) in scenario A, which was found comparable to that obtained in scenario D, wherein harsh and expensive thermochemical pretreatment was employed. Besides that, relatively higher methane yield of 209–257 dm 3 /kg TOCR (Total organic carbon removal) obtained in scenario A as compared to other scenarios (67.5–238 dm 3 /kg TOCR ) improved the overall energy efficiency of the studied concept. The energetic assessment showed lowest total energy output (859.6–1322.7 kwh) in scenario B and C as compared to other scenarios (1041.8–1583.9 kwh), thereby confirming their incompetence in coupled bioenergy production. This study, therefore presents an economically and energetically sustainable approach for pretreatment and bioenergy production that could help in overcoming the constraints hindering the commercialization of cellulosic ethanol. The study also opens up possibility for development of coupled aquatic weeds-based wastewater treatment and bioenergy production system for an efficient exploitation of the phytoremediation property of aquatic weeds.